Antifungal activity test of single clove garlic and single clove black garlic (Allium sativum L.) against Trichophyton rubrum - Minami, Gabriella Stephanie; Zakiah, Mistika; Mahyarudin, Mahyarudin (Jurnal Pendidikan Informatika dan Sains, 2024)
Dermatophytosis is a fungal infection of the skin surface which mostly caused by Trichophyton rubrum in Indonesia. Single clove garlic (Allium sativum) exhibits superior antimicrobial properties compared to conventional garlic. When incubated at a specific temperature and humidity (70°C, 90%), single clove garlic transforms into black garlic, further enhancing its antimicrobial efficacy. This research aims to evaluate the antifungal properties of extracts from both single clove garlic and single clove black garlic against Trichophyton rubrum. The antifungal activity was tested by disc diffusion at concentrations of 25%, 50%, 75% and 100%. No inhibition zones were observed in the group treated with single clove garlic extract at concentrations of 25%, 50%, 75%, and 100%, nor with single clove black garlic extract at a concentration of 25%. However, single clove black garlic extract at concentrations of 50%, 75%, and 100% demonstrated inhibition zones ranging from 16.4 to 21.8 mm, indicating strong to very strong antifungal activity. Single clove garlic exhibited no antifungal activity against Trichophyton rubrum. In contrast, single clove black garlic demonstrated antifungal activity against Trichophyton rubrum at concentrations of 50%, 75%, and 100%, with an effective dose starting at 50%. These findings indicate that black garlic extract may serve as a potential alternative treatment for dermatophyte fungal infections, particularly those caused by Trichophyton rubrum.